4th International Reindeer/Caribou Symposium, 22-25 August 1985, Whitehorse, Canada - Skjenneberg (ed. in chief), Sven (Rangifer, 1986)
Proceedings - the 4th Int. Reindeer/Caribou Symposium, Whitehorse, Yukon, Canada, 22-25 August, 1985